MicroRNA profiling reveals important functions of miR-125b and let-7a during human retinal pigment epithelial cell differentiation. (January 2020) - Shahriari, Fatemeh; Satarian, Leila; Moradi, Sharif; Zarchi, Ali Sharifi; Günther, Stefan; Kamal, Aryan; Totonchi, Mehdi; Mowla, Seyed-Javad; Braun, Thomas; Baharvand, Hossein
Abstract: Retinal pigment epithelial (RPE) cells are indispensable for eye organogenesis and vision. To realize the therapeutic potential of in vitro -generated RPE cells for cell-replacement therapy of RPE-related retinopathies, molecular mechanisms of RPE specification and maturation need to be investigated. So far, many attempts have been made to decipher the regulatory networks involved in the differentiation of human pluripotent stem cells into RPE cells. Here, we exploited a highly-efficient RPE differentiation protocol to determine global expression patterns of microRNAs (miRNAs) during human embryonic stem cell (hESC) differentiation into RPE using small RNA sequencing. Our results revealed a significant downregulation of pluripotency-associated miRNAs along with a significant upregulation of RPE-associated miRNAs in differentiating cells. Our functional analyses indicated that two RPE-enriched miRNAs (i.e. miR-125b and let-7a) could promote RPE fate at the expense of neural fate during RPE differentiation. Taken together, these mechanistic interrogations might shed light on a better understanding of RPE cell development and provide insights for the future application of these cells in regenerative medicine. Highlights: MicroRNAs are dynamically regulated during hESC differentiation into RPE. miR-204, -125b, −211, and let-7 family are the most abundant miRNAs in RPE. miR-204, -125b, −211, and let-7 miRNAs constitute more than half of the RPE miRNome. miR-125b-5p and let-7a-5p support the maintenance of RPE by upregulating MITF. miR-125b-5p and let-7a-5p enhance the differentiation of RPE from hESCs.